Anticipation of Normal Asthenia Syndrome of Faith in Congregation: Implementation of Psalm 4:1-9 - Rosmey Meriaty br. Sormin; Naomi Sirait; Andar Gunawan Pasaribu (International Forum of Researchers and Lecturers, 2024)
The Asthenia Syndrome Normality (ASN) of Faith is a phenomenon of weakness and fatigue in the realm of faith. Normal faith asthenia syndrome can evolve into abnormal forms. The research method employed is qualitative, drawing from literature on asthenia. The proposed developmental model is the